Effects of short-term plyometric training on lower extremity power, strength, endurance and kicking speed in male college soccer players / Eng Hoe Wee, Aik Hau Boon and Hui Yin Ler - Eng, Hoe Wee; Aik, Hau Boon; Huui, Yin Ler (Universiti Teknologi MARA, 2023)
This study investigated the effects of 6 weeks plyometric training [PT] on leg power and strength and kicking velocity. Nineteen male soccer players (age = 19.2 + 1.3 years) were randomly assigned into control group (CG, n=9) and experimental group (EG, n=10) after pre-tests on the five measures (maximal ball velocity (MBV), squat jump [SJ], countermovement jump [CMJ], squat test [ST], and isokinetic leg strength.). Both groups performed similar bi-weekly soccer training program (technical, tactical, and matches) together, and EG also performed PT twice per week. Wilcoxon signed-rank test on the pre-test median scores between EG and CG showed insignificant differences in kicking speed, leg power, leg strength, and leg endurance. However, significant post-test comparison was found for leg strength (U=19.0, p=0.034) between EG and CG. In the pre and post-test comparisons, EG showed significant gains relative to CG in MBV (p < .05, d = 1.37), leg power (p < .05, d = 0.97), and leg strength (p < .05, d = 0.95) while CG only achieved significant improvement in the MBV (P < .05, d = 1.16). It concludes that adding plyometric training to regular soccer training improved leg strength in college soccer players.